Emmanuel-Philibert de Pingon (1525-1582): A Biography and a Critical Edition - Corey, Alexandra Mckenzie (Trinity College Dublin. School of Lang, Lit. & Cultural Studies. Discipline of French, 2023)
This thesis presents the first detailed biography of the Savoyard poet, diplomat, and historiographer, Emmanuel-Philibert de Pingon (1525-1582) and the first critical edition of a selection of his works. Pingon wrote prolifically, but his writings have remained largely in manuscript form. He was a key observer of the major political, religious, and cultural developments of the period, both within the Duchy of Savoy and at a broader European level. This thesis aims to promote a better understanding of the literary and political environments of the court of Savoy in the sixteenth century and Pingon's place within them.
APPROVED
Keywords: Pingone, Emmanuele Filiberto, Baron di Cusago, 1525-1582